THE EFFECT OF TAX AVOIDANCE ON COMPANY VALUE WITH TAX SANCTIONS AS A MODERATING VARIABLE - Herlina Theodensia D. Doke; Riza Reni Yenti; Margarethy Rohanie Mbado; Yudith F. Lerrick; Melinda Melinda (ITB AAS Indonesia Surakarta, 2024)
ABSTRACT This research is quantitative research with an exploratory approach, namely an approach that uses a number of previous studies, especially the five studies above, as the most basic reference for building the agrumentation construct that the researcher will build. The data that researchers use in this article is secondary data that researchers obtained from the Indonesian Stock Exchange. The data used in this research was analyzed using the smart PLS 4.0 analysis tool. The result int this article show. the two hypotheses that the researcher argued in the research methodology section, namely the Tax Avoidance variable, can have a positive relationship direction and a significant influence on the Company Value variable and the Tax Sanction variable can moderate the influence of the Tax Avoidance variable on Company Value due to value. each P-Values in the two rows of the table above shows the direction of a positive relationship and a significant influence which is smaller than the 0.05 significance level, namely 0.001 on the influence of the Tax Aviodance variable on Company Value and 0.000 in the next row, namely the Tax Sanction variable can moderate the influence of the variable. Tax Aviodance on Company Value. This can be caused because Tax Avoidance can minimize expenses which makes the company's financial condition stable. Apart from that, tax sanctions are not too strict and can make companies bolder in avoiding taxes.. Thus the first and second hypotheses in this research can be accepted.